Hydrothermal synthesis of WS2/RGO sheet and their application in UV photodetector - Shelke, Nitin T.; Karche, B. R. (Journal of Alloys and Compounds, 2015)
Two-dimensional (2D) semiconductor nanomaterials hold great promises for future electronics and optics. In this paper, we report UV photocurrent response of 2D hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide prepared by using one step hydrothermal method. Few-layer WS2 and WS2/RGO nanosheets are characterized by Raman spectroscopy and HRTEM. The electric and optoelectronic properties of WS2 and WS2/RGO based UV photodetector shows a fast response of 48s and 85s and high photosensitivity (80 mu AW(-1) and 3.21 mAW(-1)) indicating that the two-dimensional composite nanostructure WS2/RGO is an important material for high performance photodetectors. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: nanosheets; UV photodetector; WS2; WS2/RGO

Ultraviolet photosensor based on few layered reduced graphene oxide nanosheets - Shelke, Nitin T.; Karche, B. R. (Applied Surface Science, 2017)
Reduced graphene oxide (RGO), a two-dimensional (2D) system, has attracted much interest in photonic applications owing to its ability to absorb light over a broad wavelength. This leads to several studies on RGO-based photosensors. In this paper, chemical oxidation of graphite was carried out at room temperature for the preparation of large area reduced graphene oxide using a modified Hummer's method. The as-prepared reduced graphene oxide was characterized by XRD, Raman spectroscopy, FESEM, and TEM to confirm the absence of impurities and to ascertain their morphology. In addition, the as-prepared reduced graphene oxide for its possible application as UV photosensor is reported. The electric and optoelectronic properties of RGO based UV photosensor shows a fast response and recovery time of 1 s and 3 s; high photoresponsitivity (3.74AW(-1)) and quantum efficiency (1274%) indicating that the graphene oxide is an important material for high performance photosensor. This work demonstrates the ultrafast photoresponse with high photoresponsivity, proving its potential as a promising material for optoelectronic devices. 2016 Elsevier B.V. All rights reserved.

Hydrothermal growth and humidity-dependent electrical properties of molybdenum disulphide nanosheets - Shelke, Nitin T.; Karle, S. C.; Karche, B. R. (Journal of Nanoscience and Nanotechnology, 2019)
In present investigation, we report humidity dependent electrical properties of molybdenum disulphide (MoS2) nanosheets. MoS2 nanosheets were prepared through a facile hydrothermal method with different reaction temperatures. The as-synthesized MoS2 nanosheets were characterized with XRD, SEM, TEM, and Raman spectroscopy, which confirmed successful preparation and rationality. Further, the humidity dependent electrical properties against relative humidity (RH) of these samples were carried out at room temperature. The results evinced that the sensors film fabricated with MoS2 nanosheets prepared at temperature 220 degrees C exhibited better performance compared to the nanosheets synthesized at 180 degrees C and 200 degrees C temperature. The RH sensing results exhibits highly sensitive, ultrafast response/recovery behaviour and outstanding repeatability than reported earlier. The excellent humidity sensing properties of the resultant MoS2 nanosheets was proved to be an excellent candidate for constructing ultrahigh-performance humidity sensor toward various applications.
Keywords: Humidity sensors; Hydrothermal method; Molybdenum Disulphide; nanosheets

Hydrothermal growth of MoSe2 nanoflowers for photo- and humidity sensor applications - Shelke, Nitin T.; Late, Dattatray J. (Sensors and Actuators A-Physical, 2019)
In the present investigation, we report the synthesis of molybdenum diselenide (MoSe2) nanoflowers by facile hydrothermal method for photo- and humidity sensor applications. The obtained samples were characterized thoroughly by x-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The XRD spectrum shows crystalline nature of the sample. Raman spectroscopy shows two prominent vibration modes of E-2 (g)1 and A(1g) at (2) over tilde 41 and (2) over tilde 83 cm(-1) respectively. The crystalline nature of the sample confirmed with the TEM. The MoSe2 nanoflowers based sensor shows high photosensitivity and good response to humidity with excellent prolong stability. The maximum photoresponsitivity of (1) over tilde 94% along with response of (4) over tilde0 ms and recovery time of (4) over tilde8 ms were observed for the sample. In case of humidity sensor, response time of (5) over tilde3 s and recovery time of (1) over tilde3 s with maximum sensitivity -74% were observed under humidity environments. It suggests that, MoSe2 nanoflowers appear as a potential candidate for constructing high-performance nanoelectronics devices. (C) 2019 Elsevier B.V. All rights reserved.

Photoresponse properties of CdSe thin film photodetector - Shelke, Nitin T.; Karle, S. C.; Karche, B. R. (Journal of Materials Science-Materials in Electronics, 2020)
In the present investigation, the performance of highly sensitive photodetector based on CdSe thin film has been demonstrated. The cadmium selenide (CdSe) films were deposited successfully by spray pyrolysis method on glass substrate. The as-deposited films were used as visible light detector. Further, the structural, morphological, and optical properties of CdSe films were investigated through X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy, and optical absorption spectrophotometer. The XRD studies show that the produced samples are polycrystalline in nature. A UV-Visible absorbance spectrum indicates direct allowed transition with bandgap about 1.75 eV. The SEM micrographs depict uniformly distributed well defined uneven hexagonal grains. The CdSe film-based photodetector exhibits high responsivity, detectivity and shows an ultrafast photoresponse. The excellent photoresponse and high photosensitivity of CdSe film makes it a strong candidate for high-performance photodetectors.